A Comparative Study of Organizations for the Development and Contributions in Management and Leadership Sectors in Bangladesh - Nur, Ifat (Global journal of Business and Integral Security, 2023)
Background The aim of this study was to investigate the impact of economic, technological, and political factors on leadership and management for organizational development in Bangladeshi organizations. The objectives of this study were set in divisions in which a part is focused on investigating the cultural impact, technological impact, and political-economic impact on the leadership and management exercises of Bangladesh and other developing countries. A few pieces of past literature have been gone through to understand the context of the leadership and management approaches in developing countries. Methods The research has followed the primary data collection process and quantitative data analysis techniques. A survey of 150 participants regarding leadership and management roles is conducted to conduct the study and reach results. Positivism research philosophy is used in the study to achieve the factual knowledge to properly conduct the quantitative study and reach effective results. A purposive sampling technique is followed in this research to collect the survey participants based on the particular research criteria. Moreover, an exploratory study design is followed in the study to explore the target area with a wide range of research areas. The survey results have indicated that the leaders and managers of Bangladeshi organizations cannot properly manage the multi-cultural environment of the organization. Results As Muslim cultural people are present in the majority number in organizations, the leaders and managers are influenced by this cultural term. Moreover, there is a lack of technical infrastructure in developing countries such as India, Pakistan, and Bangladesh. It is observed that India is planning to improve the technical infrastructure so that it can be included in the organizational processes to make improvements in the leadership and management functions. The policy development process is also not transparent and, therefore, the leaders and managers cannot properly comply with them. Discussion and conclusion It is recommended that the leaders and managers of Bangladeshi organizations should understand the multi-cultural factors and properly design them in the organizations. Moreover, they must include the employees in the decision-making process of the organization to achieve organizational development. The policy development process should be made transparent so that the leaders, managers, and other organizational members can understand and follow them clearly. Lastly, the leaders and managers must carry out regular internal and external environmental analyses to be aware of the changing organizational needs. It would help in the proper allocation of resources and achieving organizational development.